Physiotherapy through pseudo-competitive games : gameplay design - Mohamad Iswandy Mohamad Yaacob (2017)
As the world population reaches the seven billion mark and with technology progressing day by day, there is a perpetual rise in demand for innovative creations to add convenience and ease our daily lives1. While a window using an interface may be a normal application in today’s world, the use of advanced technology software implementation is prevalent for lives to be more productive and convenient. As society faces the challenges associated with an aging population, the number of elderly that requires nursing care is increasing. Leading a sedentary lifestyle may contribute to deteriorating physical capabilities. People with chronic arm impairment should exercise intensely to regain their abilities, but frequently lack motivation, leading to poor rehabilitation outcome. Little is known about how they affect motivation. Thus, pseudo-competitive games with appropriate man-machine interface can help to promote active lifestyle and graceful aging for the elderly. Such games can be beneficial for rehabilitative purpose for the general well-being of the elderly. This project focuses on the gameplay protocol design as well as definition of the scope and boundary of what is reasonable and practical in the scenario described.